2018
DOI: 10.1021/acsabm.8b00166
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot Surface-Chemistry-Dependent Ag Release Governs the High Antibacterial Activity of Ag-Metal–Organic Framework Composites

Abstract: Nanocomposites and hybrid materials of Ag−1,3,5benzenetricarboxylic acid metal−organic frameworks (MOFs) with Sand N-carbon quantum dots (CQDs) were synthesized and evaluated for their antibacterial activity against representative Gram-positive (Bacillus subtilis) and Gram-negative (Escherichia coli) bacterial strains using the qualitative disk-diffusion approach and the quantitative minimum inhibitory concentration test. The composites and hybrids were found to be nontoxic to living cells. The composite forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 66 publications
0
54
0
1
Order By: Relevance
“…Similar shi values have been previously reported for water molecules in many different systems. 7,53,54 Particularly, Gul-E-Noor et al assigned proton resonances of water molecules in the range of d 1 H ¼ 15-4 ppm for Cu 3 (BTC) 2 MOF structures. 55,56 The main difficulty in studying the chemical functionalization of the ligand in the Cu(II) complex obtained in water is that single crystals for structural characterization could not be obtained.…”
Section: Solid-state Nmr Assignment In Cu(ii)-4pyridinecarboxaldehydementioning
confidence: 99%
“…Similar shi values have been previously reported for water molecules in many different systems. 7,53,54 Particularly, Gul-E-Noor et al assigned proton resonances of water molecules in the range of d 1 H ¼ 15-4 ppm for Cu 3 (BTC) 2 MOF structures. 55,56 The main difficulty in studying the chemical functionalization of the ligand in the Cu(II) complex obtained in water is that single crystals for structural characterization could not be obtained.…”
Section: Solid-state Nmr Assignment In Cu(ii)-4pyridinecarboxaldehydementioning
confidence: 99%
“…Inorganic [ 4–9 ] and carbon‐based nanomaterials, [ 9–12 ] polymers and peptides, [ 13,14 ] as well as light‐activated nanomaterials [ 15,16 ] have emerged as promising antimicrobial agents for treatment and prevention of infectious diseases. Particularly silver colloids can inhibit growth of pathogens at very low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the addition of polyamines [ 16 , 62 ], amino acids [ 63 , 64 , 65 , 66 , 67 ], or biomass such as plant leaves and fungi [ 68 , 69 , 70 , 71 , 72 , 73 , 74 ], food [ 75 , 76 , 77 , 78 , 79 ], and industrial [ 80 ] and waste derivatives [ 81 , 82 ], among others, have been used for the preparation of doped CDs. In this context, two independent comparative studies from the Kang [ 83 ] and Bandosz [ 84 ] research groups highlighted that N- or S-doped CDs exhibit very different antibacterial properties. The authors demonstrated that the increased S-doping content correlates with an increase in repulsive forces between the less positively charged CDs (when compared to N-doped CDs) and the negatively charged bacterial surfaces.…”
Section: Cds As Bacteria Targeting and Antibacterial Agentsmentioning
confidence: 99%